AZIMUTHS RADIATION RISK DEGREE APPRAISAL FOR THE POPULATION LIVING IN AREA OF THE NUCLEAR POWER PLANTS LOCATION - Avagyan, R. M.; Haroutyunyan, G. H.; Atoyan, V. A.; Hovsepyan, A. V.; Pyuskyulyan, K. I.; Chubaryan, E. V. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2009)
The data of radioactive emission from the Armenian NPP in atmosphere in a mode of normal operation and in emergency situations are presented. The technique of the azimuths (sectors) radiation risk calculation for the population, living in area of nuclear power plants location, is proposed. The values of azimuths radiation risk for area of the Armenian NPP location are calculated. The analysis of the obtained values is carried out. The azimuths, most significant from the point of view of radiation monitoring organization in area of the Armenian NPP location are determined, as well as concentration of forces and means for the population protection in case of possible accidents.
Keywords: monitoring, emission; radiation; protection; accident; azimuth